Micro-, small-, and medium-sized enterprises using structural funds - Peszko, Agnieszka (Managerial Economics, 2014)
Numerous academic publications are currently concentrating on the role that structural funds play in financing small- and medium-sized enterprises, as well as the level of possibili- ties and the benefits that such enterprises may be able to gain as a result of structural funding. The high formal and substantive requirements for access to these funds, which causes that these sources are not available for all enterprises, often are skipped. The objective of this paper is to answer the question of what attributes are typical for micro-, small-, and medium-sized enterprises that fulfilled all requirements and received structural funds subsidies. Additionally, this article presents opinions expressed on structural fund access barriers by entrepreneurs. The research (whose results are discussed in this paper) was conducted among micro-, small-, and medium-sized enterprises of Malopolska received structural funds subsidies. This article demonstrates that access to structural funding is limited to a particular group of enterprises.